Aggressive Behavior and Performance in the Tegu Lizard Tupinambis merianae - Herrel, Anthony; Andrade, Denis V. [UNESP]; Carvalho, José Eduardo de; Brito, Ananda; Abe, Augusto Shinya [UNESP]; Navas, Carlos (Univ Chicago Press, 2009)
Aggression is an important component of behavior in many animals and may be crucial to providing individuals with a competitive advantage when resources are limited. Although much is known about the effects of catecholamines and hormones on aggression, relatively few studies have examined the effects of physical performance on aggression. Here we use a large, sexually dimorphic teiid lizard to test whether individuals that show high levels of physical performance (bite force) are also more aggressive toward a potential threat (i.e., a human approaching the lizard). Our results show that independent of their sex, larger individuals with higher bite forces were indeed more aggressive. Moreover, our data show that individuals with higher bite forces tend to show decreased escape responses and are slower, providing evidence for a trade-off between fight and flight abilities. As bite force increased dramatically with body size, we suggest that large body size and bite force may reduce the threshold for an individual to engage in an aggressive encounter, allowing it to potentially gain or maintain resources and fight off predators while minimizing the risk of injury.